Trivalent Actinide Ions Showing Tenfold Coordination in Solution - Weßling, Patrik; Schenk, Tobias; Braun, Felix; Beele, Björn B.; Trumm, Sascha; Trumm, Michael; Schimmelpfennig, Bernd; Schild, Dieter; Geist, Andreas; Panak, Petra (Inorganic chemistry, 2020)
Trivalent actinides generally exhibit ninefold coordination in solution. 2,6-Bis(5,6-dipropyl-1,2,4-triazin-3-yl)pyridine (nPr-BTP), a tridentate nitrogen donor ligand, is known to form ninefold coordinated 1:3 complexes, [An(nPr-BTP)3]3+ (An = U, Pu, Am, Cm) in solution. We report a Cm(III) complex with tenfold coordination in solution, [Cm(nPr-BTP)3(NO3)]2+. This species was identified using time-resolved laser fluorescence spectroscopy (TRLFS), vibronic side band spectroscopy (VSBS), X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT). Adding nitrate to a solution of the [Cm(nPr-BTP)3]3+ complex in 2-propanol shifts the Cm(III) emission band from 613.1 to 617.3 nm. This bathochromic shift is due to a higher coordination number of the Cm(III) ion in solution, in agreement with the formation of the [Cm(nPr-BTP)3(NO3)]2+ complex. The formation of this complex exhibits slow kinetics in the range of 5 to 12 days, depending on the water content of the solvent. Formation of a complex [Cm(nPr-BTP)3(X)]2+ was not observed for anions other than nitrate (X- = NO2-, CN-, or OTf-). The formation of the [Cm(nPr-BTP)3(NO3)]2+ complex was studied as a function of NO3- and nPr-BTP concentrations, and slope analyses confirmed the addition of one nitrate anion to the [Cm(nPr-BTP)3]3+ complex. Experiments with varied nPr-BTP concentration show that [Cm(nPr-BTP)3(NO3)]2+ only forms at nPr-BTP concentrations below 10-4 mol/L whereas for concentrations greater than 10-4 mol/L the formation of the tenfold species is suppressed and [Cm(nPr-BTP)3]3+ is the only species present. The presence of the tenfold coordinated complex is supported by VSBS, XPS, and DFT calculations. The vibronic side band of the [Cm(nPr-BTP)3(NO3)]2+ complex exhibits a nitrate stretching mode not observed in the [Cm(nPr-BTP)3]3+ complex. Moreover, XPS on [M(nPr-BTP)3(NO3)](NO3)2 (M = Eu, Am) yields signals from both non-coordinated and coordinated nitrate. Finally, DFT calculations reveal that the energetically most favored structure is obtained if the nitrate is positioned on the C2 axis of the D3 symmetrical [Cm(nPr-BTP)3]3+ complex with a bond distance of 413 pm. Combining results from TRLFS, VSBS, XPS, and DFT provides sound evidence for a unique tenfold coordinated Cm(III) complex in solution—a novelty in An(III) solution chemistry.